Personality traits and foreign policy attitudes: A cross-national exploratory study. (15th January 2020) - Gravelle, Timothy B.; Reifler, Jason; Scotto, Thomas J.
Abstract: The study of foreign policy attitudes lies at the intersection of political psychology and international relations. Despite a shared interest in both fields in the psychological bases of political phenomena, research exploring the links between personality traits and foreign policy attitudes is scarce. This article pursues a set of questions intended to bring these agendas together. Do personality traits influence attitudes toward foreign policy? Are the links between personality traits and foreign policy the same, or do they differ across different national contexts? In exploring these questions, this article draws on data from a series of large-scale public opinion surveys in six western democracies: the United States, the United Kingdom, France, Germany, Canada, and Australia.